Effect of ellagic acid on some haematological, immunological and antioxidant parameters of rainbow trout (Oncorhynchus mykiss) - Yonar, S. Mise; Yonar, M. E.; Yonturk, Y.; Pala, A. (Wiley, 2014)
In this study, effect of ellagic acid on some haematological, immunological and antioxidant parameters in the blood and various tissues of rainbow trout (Oncorhynchus mykiss) were examined. Four groups of rainbow trout were fed experimental diets containing either no ellagic acid (control) or supplemented with ellagic acid at 50mg/kg diet (EA-50), 100mg/kg diet (EA-100) or 150mg/kg diet (EA-150) for 21days. Samples of the blood and tissue (liver, kidney and spleen) were collected at the end of the experiment and analysed for their haematological profile (the red blood cell count, the haemoglobin concentration and the haematocrit level), immune response (the white blood cell count, the oxidative radical production (NBT activity), the total plasma protein and total immunoglobulin level) and oxidant/antioxidant status (the malondialdehyde level, the superoxide dismutase, catalase and glutathione peroxidase activity as well as the reduced glutathione concentration). The findings of this study demonstrated that ellagic acid had a positive effect on the haematological parameters, the immune response and the antioxidant enzyme activities of the fish.
Keywords: rainbow trout; ellagic acid; haematology; immunity; oxidative stress